2019
DOI: 10.1016/j.jmb.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Cations Alter the Rate-Limiting Step of PrimPol-Catalyzed DNA Elongation

Abstract: PrimPol is the most recently discovered human DNA polymerase/primase and plays an emerging role in nuclear and mitochondrial genomic maintenance. As a member of archaeo-eukaryotic primase (AEP) superfamily enzymes, PrimPol possesses DNA polymerase and primase activities that are important for replication fork progression in vitro and in cellulo. The enzymatic activities of PrimPol are critically dependent on the nucleotidyl-transfer reaction to incorporate deoxyribonucleotides successively; however, our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Assuming that PrimPol may utilize either Mg 2+ or Mn 2+ in the cell 35,57 , the stabilization/destabilization effect may favor a particular mode for PrimPol. In agreement with this idea, a recent paper 58 demonstrated that in the presence of Mn 2+ , a conformational transition step from non-productive to productive PrimPol:DNA complexes limits the enzymatic turnover, whereas, in the presence of Mg 2+ , the chemical step becomes rate limiting. The appearance of two melting minima for wild-type PrimPol, which correspond to the ZnF and the catalytic polymerase domain, may also aid in understanding the primase mechanism of PrimPol.…”
Section: Structural Basis For the Loss Of Primase Activity But Residumentioning
confidence: 63%
“…Assuming that PrimPol may utilize either Mg 2+ or Mn 2+ in the cell 35,57 , the stabilization/destabilization effect may favor a particular mode for PrimPol. In agreement with this idea, a recent paper 58 demonstrated that in the presence of Mn 2+ , a conformational transition step from non-productive to productive PrimPol:DNA complexes limits the enzymatic turnover, whereas, in the presence of Mg 2+ , the chemical step becomes rate limiting. The appearance of two melting minima for wild-type PrimPol, which correspond to the ZnF and the catalytic polymerase domain, may also aid in understanding the primase mechanism of PrimPol.…”
Section: Structural Basis For the Loss Of Primase Activity But Residumentioning
confidence: 63%
“…Thus, the active site of PrimPol, even after the binding of both ions, appears to be less tightly organized than Pol η’s and possibly more dependent on slow thermal motion to align the catalytic groups. The slow catalytic tuning might represent the ‘rate-limiting conformational transition step’ detected for PrimPol during a pre-steady-state kinetics study 48 .…”
Section: Discussionmentioning
confidence: 98%
“…The active site of PrimPol has the following conserved key residues (compiled in Figure 7 A and Table 1 ) that have been studied in vitro : the three conserved carboxylates D 114 , E 116 , and D 280 , which are the residues that cause the covalent binding of the two-metal cations used to carry out the above mentioned nucleotidyl transferase reaction [ 12 , 77 , 107 ]. Mn 2+ is the preferred metal for PrimPol activities in vitro [ 12 , 75 , 77 , 108 , 109 , 110 ], despite having lesser fidelity than with Mg 2+ [ 75 , 109 , 110 ]. Mutations of the three carboxylates for alanine erase primase and polymerase activities [ 12 , 77 ].…”
Section: Structure and Regulation Of Human Primpolmentioning
confidence: 99%